Autologous dura mater grafts in reconstructive surgeries for breast cancer patients - D. Sh. Dzhabrailova; A. D. Zikiryakhodzhaev; F. N. Usov; M. V. Starkova; D. V. Bagdasarova; I. S. Duadze (ABV-press, 2021)
Reconstructive surgeries have long been considered as an essential part of rehabilitation of breast cancer patients. The majority of patients tend to choose one-stage reconstruction, because this type of surgery ensures rapid emotional and physical recovery. Due to the lack of subcutaneous fat in a substantial proportion of cases, which leads to postoperative complications, the most common surgical tactics now is simultaneous reconstruction after subcutaneous mastectomy with subpectoral implant location and strengthening of the lower breast slope using different materials. So far, there has been no gold standard material for secure covering of the lower pole of the implant. Autologous acellular dura mater grafts are a promising material for breast reconstruction. Studies evaluating biointegration, compatibility, inertness, reactivity, and cost effectiveness of autologous acellular dura mater grafts have determined feasibility of using these grafts in reconstructive surgeries.